PEMANFAATAN LIMBAH RUMAH TANGGA SEBAGAI SUMBER HARA TANAMAN ANGGREK DENDROBIUM - Kusmiadi, Riwan; Aini, Sitti Nurul; Lestari, Tri (Universitas Trilogi, 2023)
Rice wastewater and banana peel extract contain nutrients needed by orchid plants such as carbohydrates, nitrogen, phosphorus, magnesium, potassium, sulfur, iron, and vitamin B1. The use of these two materials as a source of fertilizer can reduce the use of inorganic fertilizers and be more environmentally friendly. This experiment aims to obtain the best frequency of watering rice wastewater and banana peel extract for Dendrobium orchid plants' vegetative and generative growth. Giving rice wastewater every 4 days has the best vegetative (plant height) and generative growth (flowering initiation) when compared with intervals every 2 and 6 days. The application of banana peel extract shows that treatment every 10 days has the best vegetative (plant height) and generative growth when compared to the treatment every 5 days and 10 days. There is no real interaction between rice wastewater and banana peel extract. Too frequent application of both rice wastewater and banana peel extract causes orchid plants to experience growth inhibition due to high moisture on media and plant surface.